2018
DOI: 10.1002/ccd.27838
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and etiologies of 30‐day readmissions in patients with non‐ST‐elevation acute coronary syndrome

Abstract: Background Despite improvements in acute care and survival after non‐ST‐elevation acute coronary syndrome (NSTE‐ACS) hospitalization, early readmissions remain common, and have significant clinical and financial impact. Objectives Determine the predictors and etiologies of 30‐day readmissions in NSTE‐ACS. Method The study cohort was derived from the National Readmission Database 2014 identifying patients with a primary diagnosis of NSTE‐ACS using ICD9 code. Results We identified a total of 300,269 patients adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 17 publications
3
9
1
1
Order By: Relevance
“…An analysis of the National Readmissions Database revealed that CCI≥3 was the foremost predictor of 30-day readmission among patients with non-ST elevation ACS. 27 Finally, we also report that comorbidity burden may have an important health economic impact in patients with ACS, we observe an incremental increase in the median adjusted cost of hospitalization of ACS patients with increase in comorbidity burden ($17675 in CCI=0 to $21139 in CCI≥3). As expected, the median length of stay also increased with increasing comorbidity burden (5 days for CCI≥3 group as compared to 3 days for CCI=0).…”
Section: Discussionsupporting
confidence: 53%
“…An analysis of the National Readmissions Database revealed that CCI≥3 was the foremost predictor of 30-day readmission among patients with non-ST elevation ACS. 27 Finally, we also report that comorbidity burden may have an important health economic impact in patients with ACS, we observe an incremental increase in the median adjusted cost of hospitalization of ACS patients with increase in comorbidity burden ($17675 in CCI=0 to $21139 in CCI≥3). As expected, the median length of stay also increased with increasing comorbidity burden (5 days for CCI≥3 group as compared to 3 days for CCI=0).…”
Section: Discussionsupporting
confidence: 53%
“…This is consistent with other literature showing that women have a greater risk of 30-day readmission than men following hospitalization for acute myocardial infarction. 2 , 3 , 13 16 However, one study reported that younger women (<65 years) had higher 30-day readmission rates following an acute myocardial infarction compared to men, 2 but this same study, along with an additional study, 1 showed that readmission timing within 30 days was similar between sexes. Of ACS patients readmitted within 30 days, we found that females had roughly twice the odds of early readmission relative to men, suggesting a sex disparity in readmission timing.…”
Section: Discussionmentioning
confidence: 95%
“…We found that CHF was the overall leading primary diagnosis (34%) as well as most common cardiac cause (65.7%) of 30‐day readmission. The higher rate of CHF hospitalization in the TAVR with ACS cohort is likely related to the influence of ACS on heart failure 37 . Early follow up after discharge and interventions proven to be effective in reducing the burden of heart failure rehospitalizations may be valuable in reducing 30‐day readmissions after TAVR with ACS 38 …”
Section: Discussionmentioning
confidence: 99%